The rise and fall of the Normalarbeitsverhältnis in Germany - Toni Pierenkemper (Institute for the Study of Labor (IZA), 2009)
The following paper attempts to trace the construction of the standard employment contract in Germany from the beginning of the 19th century onwards. It was from this point in time that wage labour slowly came into being and later on developed more broadly. At first, state regulations were implemented to protect the workforce against exploitation by industrial entrepreneurs (laws on working hours, trading regulations etc.). Later on, as the state grew wealthier, the opportunity arose to create a social insurance system, to protect working people against basic risks. Finally, workers' and entrepreneurs' organisations participated in the market and collectively agreed on regulations of employment relationships. Alongside the consolidation of the welfare state, this type of employment was reinforced in Germany in the 20th century and finally developed into the modern concept of the standard employment contract. However, due to the forces of globalization and the dynamics of capitalist market economies, it seems that the standard employment contract has turned into an obstacle in the way of modern economy's progress. Its achievements are threatened in many ways: the future will seemingly be determined by increasing work flexibility, rising working hours, falling income and increasing unemployment rates, rendering the standard employment contract anachronistic and obsolete.
urn:nbn:de:101:1-2009033016
Keywords: N33; N34; 330; Economic history; standard employment; Germany; Arbeitsverhältnis; Arbeitswelt; Arbeitsmarktpolitik; Geschichte; Deutschland